Resilience, Return, and Inclusive Governance in Post-Assad Syria - Ismail, A. (Resilience and Inclusive Politics in the MENA Region, 2025)
The fall of the Assad regime in late 2024 has opened a new phase in Syria’s transition, marked by urgent political negotiations and the challenge of rebuilding inclusive governance. While international discussions increasingly address power-sharing, decentralisation and gender inclusion, the return and reintegration of displaced Syrians remains a critically underexamined dimension. More than one million people have already returned spontaneously. Over 300,000 from neighbouring countries and almost 900,000 internally displaced, placing immediate pressure on state institutions and local authorities. This article argues that return and reintegration must be understood not simply as humanitarian processes but as central pillars of inclusive governance and long-term resilience. It examines how reintegration intersects with political participation, gender equality, property rights, legal identity documentation and the ability of returnees to access services and shape local decision-making. The analysis highlights the risks of repeating pre-war exclusionary practices, particularly through discriminatory property laws, limited civil registration mechanisms and the marginalisation of women and civil society actors. The article also assesses the role of external actors whose fragmented engagement risks deepening local divides, and emphasises the need for governance-focused approaches that support equitable reintegration. Local governance is identified as a critical arena, yet inconsistent practices and limited capacity currently mark it. The paper concludes that reintegration is a key benchmark for Syria’s transition: without policies that protect rights, ensure participation and embed inclusion into institutional reforms, prospects for resilience and sustainable peace will remain fragile.